Kinetic Insights into the Antioxidant Effect of Isatin-Thiosemicarbazone in Biodiesel Blends - Karakullukçu, Nalan Türköz; Muğlu, Halit; Yakan, Hasan; Yılmaz, Volkan Murat; Marah, Sarmad; İnce, İkbal Agah (MDPI AG, 2024)
Biodiesel has several drawbacks, such as being prone to oxidation, having reduced stability, and having limited storage time. Antioxidants compatible with biodiesel are being used to address its drawbacks. Utilizing antioxidants effectively improves the quality of biodiesel. Enhancing the quality of biodiesel for use as a clean energy source benefits both the global economy and ecology. Therefore, we believe that our work will contribute to the advancement of the worldwide industry. The study used blends consisting of 20% biodiesel and 80% diesel fuel. Isatin-thiosemicarbazones were tested as additives in blends at a concentration of 3000 parts per million (ppm) using an oxifast device. Comparing them to the chemical antioxidant Trolox. FT-IR, DSC, and TGA were used to characterize these samples. DSC measured sample crystallization temperatures (Tc). Samples with antioxidants showed decreased values compared to the non-antioxidant diesel sample D100. Several DSC tests were conducted to determine the antioxidant strengths of various samples. The results showed that the FT-IR spectrum's antioxidant effect regions grow clearer with antioxidants. The extra antioxidant is effective. Biodiesel's oxidative stability improves with isatin-thiosemicarbazones at varying concentrations. The kinetics of thermal decomposition of isatin-thiosemicarbazones under non-isothermal conditions have been determined using the Kissinger, Ozawa, and Boswell techniques. The activation energies of compounds 1 and 2 were calculated 137–147 kJ mol-1 and 173–183 kJ mol-1, respectively.
Keywords: Thiosemicarbazones; Energy; thiosemicarbazones; biodiesel; RM1-950; oxidative stability; Article; Oxidative Stability; kinetic study; Biodiesel; Therapeutics. Pharmacology; Kinetic Study; energy; 7. Clean energy; 13. Climate action